Depression During COVID-19 Quarantine in South Korea: A Propensity Score-Matched Analysis - Kim, Yongjoo; Kwon, Hye-Young; Lee, Seungyoung; Kim, Chang-Bo (Frontiers in Public Health, 2022)
Background: Quarantine, a public health measure used to control the coronavirus disease 2019 (COVID-19) pandemic, has been linked to an increased risk of developing adverse psychological sequelae. This study sought to investigate whether quarantining during the COVID-19 pandemic was associated with depression among Koreans. Methods: Data were obtained from the Seoul COVID-19 Study of Quarantine (SCS-Q) and 2019 Korea Community Health Survey (KCHS). Using propensity scores estimated based on sociodemographic and health conditions, 919 individuals undergoing quarantine in the SCS-Q were matched with 919 individuals who did not experience quarantine in the 2019 KCHS. Depressive symptoms were measured using the Korean version of the Patient Health Questionnaire-9 (PHQ-9), where major depression is defined as a PHQ-9 score ≥10. Logistic regression models were adjusted for sociodemographic and health-related factors. Results: Depression prevalence was higher in quarantined individuals than in the control group (7.8% vs. 3.8%, p<0.001). Logistic regression analyses revealed that quarantining was associated with higher likelihoods of having major depression (odds ratio [OR]=2.28, 95% confidence interval [CI]: 1.49, 3.51) after adjusting for relevant covariates. Limitations: Due to online nature of the SCS-Q, this study included a limited number of elderly participants, limiting the generalizability of the findings to the general Korean population. Conclusions: The findings suggest that Koreans undergoing COVID-19 quarantine are at higher risk of depression. While further investigation is warranted, public health measures to control infectious disease outbreaks, such as quarantine, would benefit from incorporating strategies to address unintended adverse psychological effects, such as depression.